Search for Resonant Diphoton Production with the D0 Detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Konrath, J. -P.; et al. (Amer Physical Soc, 2009)
We present a search for a narrow resonance in the inclusive diphoton final state using similar to 2.7 fb(-1) of data collected with the D0 detector at the Fermilab Tevatron p (p) over bar Collider. We observe good agreement between the data and the background prediction, and set the first 95% C. L. upper limits on the production cross section times the branching ratio for decay into a pair of photons for resonance masses between 100 and 150 GeV. This search is also interpreted in the context of several models of electroweak symmetry breaking with a Higgs boson decaying into two photons.